Study of mucoadhesive microsphere of pirfenidone for nasal drug delivery (Asian Journal of Pharmaceutics (AJP), 2014)
The present research work involves formulation development and evaluation of nasal mucoadhesive microsphere in viewto, improve bioavailability and reduce dosing regimen. Microspheres were prepared by spray drying and cross-linkingmethod using chitosan and HPMC K4M, using 32 central composite design. Microspheres were evaluated for particlesize, drug content, swelling ability, and percentage yield. Compatibility was checked by doing Fourier transform infraredspectroscopy and Differential scanning calorimetry study. The polymorphism and particle shape were studied by X-raydiffraction and scanning electron microscopy. The average particle size of spray-dried and cross-linked formulations werefound in the range between 20-50 Î¼m and 30-60 Î¼m with percent mucoadhesion in the range of 80%-90% and 60-70%,respectively. In vitro drug release was found to be proportional to drug to polymer ratio. In vitro drug release for optimizedformulation, that is, (F1), for spray-drying method and cross-linking method was found to be 88.73% and 70.93% at theend of 6 h, respectively. Release of drug from microspheres followed non-Fickian diffusion kinetics. Ex vivo studies wereperformed with sheep nasal mucosa for mucoadhesion, histopathological study, and drug permeation. The histopathological study indicates nonirritant nature of microsphere. The microspheres were found to be stable at accelerated storage conditions for 1 month, as per International Conference of Harmonisation guidelines.